Structure Of Human Skeleton Exhibits The Mysterious Love Of Allah (Swt) To Prophet Muhammad (Saw) - Mohammad Abul Hossain (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
This study presents a scientific explanation of a very important verse (Ayat), 95:4 in the holy Qur’an. The verse is in sura At-Tin, states that: ﻟَﻘَﺪْ ﺧَﻠﻘْﻨَﺎ اﻹِﻧﺴَﺎنَ ﻓِﻲ ٲَﺣْﺴَنِ ﺗَﻘْﻮِﻳﻢِ :